First report of phthalate acid esters (plasticizers) in blubber of southern right whales (Eubalaena australis) from Península Valdés, Argentina - Luciana Gallo; Melina Paola Michlig; Maria Rosa Repetti; Agustina Donini; Adrian E. Rodriguez; Mariano Sironi; Marcela M. Uhart (Polar Biology, 2026)
Phthalate acid esters (PAEs) are widely used plastic additives that have become ubiquitous contaminants in marine environments. Filter-feeding baleen whales may be exposed to these pollutants through water, prey or ingested plastic debris. While macroplastics have been reported in the gut of a southern right whale (SRW, Eubalaena australis ), exposure to PAEs has not been assessed. Here, we quantified three lipophilic PAEs, dimethyl phthalate (DMP), dibutyl phthalate (DBP), and di-2-ethylhexyl phthalate (DEHP), in the blubber of 13 SRWs (three calves, three juveniles and seven adults) stranded in 2021 at Península Valdés, Argentina. More than 90% of samples contained detectable PAE levels, and 46.2% were above quantification limits. DEHP and DBP were the most prevalent compounds (61.5% and 30.8%, respectively), although the biological significance of the detected concentrations remains uncertain. This is the first report of PAEs in SRW blubber and suggests potential mother-calf transfer, highlighting exposure of Southern Hemisphere mysticetes to plastic-derived chemicals.

Adsorption, degradation, and synergistic effects of pesticides in biomixtures containing vermicompost from agricultural and urban waste - Aldana Carolina Clebot; Florencia Valentina Magni; Maria Rosa Repetti; Cristina Susana Zalazar; Maria Emilia Fernandez (Journal of Water Process Engineering, 2025)

Bio-transformation of poultry litter and activated sewage sludge to produce biomixtures for the remediation of water polluted with pesticides - Aldana Carolina Clebot; Maria Emilia Fernandez; Florencia Valentina Magni; Maria Rosa Repetti; Cristina Susana Zalazar (Chemosphere, 2024)

Spatial distribution of pesticides in surface water of the Estacas stream (Argentine Espinal region) associated with crop production - Natalia Veronica Van Opstal; Emmanuel Adrian Gabioud; Mariela Soledad Seehaus; Ramiro Joaquin Pighini; Maria Rosa Repetti; Marcelo German Wilson; Ana Beatriz Wingeyer; Alejandra Lorena Cuatrin; Luciana Maria Regaldo; Ana Maria Gagneten; Maria Carolina Sasal (Environmental Science and Pollution Research, 2023)

Quality of the surface water of a basin affected by the expansion of the agricultural frontier over the native forest in the Argentine Espinal region - Natalia Verónica Van Opstal; Mariela Soledad Seehaus; Emmanuel Adrian Gabioud; Marcelo German Wilson; Flavio José Galizzi; Ramiro Joaquin Pighini; Maria Rosa Repetti; Luciana María Regaldo; Ana María Gagneten; María Carolina Sasal (Environmental Science and Pollution Research, 2022)

Enzyme Activities as Indicators of Soil Quality: Response to Intensive Soybean and Rice Crops - Andrés M. Attademo; Juan C. Sanchez-Hernandez; Rafael C. Lajmanovich; Maria Rosa Repetti; Paola M. Peltzer (Water, Air, & Soil Pollution, 2021)